1998
DOI: 10.1212/wnl.50.2.466
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of high‐dose riboflavin in migraine prophylaxis A randomized controlled trial

Abstract: A deficit of mitochondrial energy metabolism may play a role in migraine pathogenesis. We found in a previous open study that high-dose riboflavin was effective in migraine prophylaxis. We now compared riboflavin (400 mg) and placebo in 55 patients with migraine in a randomized trial of 3 months duration. Using an intention-to-treat analysis, riboflavin was superior to placebo in reducing attack frequency (p = 0.005) and headache days (p = 0.012). Regarding the latter, the proportion of patients who improved b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
249
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(272 citation statements)
references
References 18 publications
9
249
2
7
Order By: Relevance
“…Menadione and ascorbate together can act as complex IV substrates and sustain mitochondrial ETC respiration when complex III is compromised [79]. Other compounds that enhance mitochondrial ETC and oxidative phosphorylation include nicotinamide, a precursor to the complex I substrate, nicotinamide adenine dinucleotide, and riboflavin, a precursor to the complex II substrate, flavin adenine dinucleotdie [84]. While outcomes of research on these molecules have shown promising potential in preclinical studies, their efficacy clinically is unlikely to be substantial as they target specific components of the bioenergetic system instead of the entire system.…”
Section: Mitochondrial Bioenergetics As a Therapeutic Targetmentioning
confidence: 99%
“…Menadione and ascorbate together can act as complex IV substrates and sustain mitochondrial ETC respiration when complex III is compromised [79]. Other compounds that enhance mitochondrial ETC and oxidative phosphorylation include nicotinamide, a precursor to the complex I substrate, nicotinamide adenine dinucleotide, and riboflavin, a precursor to the complex II substrate, flavin adenine dinucleotdie [84]. While outcomes of research on these molecules have shown promising potential in preclinical studies, their efficacy clinically is unlikely to be substantial as they target specific components of the bioenergetic system instead of the entire system.…”
Section: Mitochondrial Bioenergetics As a Therapeutic Targetmentioning
confidence: 99%
“…ATP was found to be reduced in the occipital lobe of MwoA patients, however, ATP remains to be measured in MwA patients. Additional evidence supporting a disturbed energy metabolism in migraine, comes from pharmacological studies showing the effects of metabolic enhancers, such as riboflavin and coenzyme Q10 (both with a well defined role in mitochondrial membrane generation of ATP), in migraine prophylaxis (65)(66)(67)(68). It is worthy of note that the therapeutic response to riboflavin was associated with specific mitochondrial DNA haplogroups (69).…”
Section: Functional Paradigmmentioning
confidence: 99%
“…Merck (rizatriptan) went for a quicker onset of action. In two RCTs rizatriptan had a quicker onset of action than sumatriptan [13,14], whereas this was not the case in one RCT published much later [25]. Almirall (almotriptan) probably went for superior efficacy and for less AEs.…”
Section: Understanding a Paper On Drug Trials In Migrainementioning
confidence: 99%
“…The whole process is complicated and is in most cases funded and controlled by the pharmaceutical industry. There are, however, exceptions to this general rule, for example a RCT on riboflavin for migraine prophylaxis [14], which was conceived and funded independently.…”
Section: How a Clinical Trial In Migraine Is Donementioning
confidence: 99%